A Selective and Reversible Fluorescent Probe for Cu2+ and GSH Detection in Aqueous Environments. Issue 12 (23rd March 2023) - Wang, Zaiwu; Li, Zuyao; Huang, Junhao; Han, Shu; Li, Xueming; Wang, Zizhou
Abstract: Cu 2+ and Biothiols play a critical role in diverse biological processes in organisms. Herein, we reported using a well‐known ESPT molecule 2‐(2'‐Pyridyl)benzimidazol(PBI ) as a fluorescent probe to detect Cu 2+ and GSH in aqueous solution. PBI presented a rapid fluorescence "ON‐OFF" response on Cu 2+ over other metal cations, with a low detection limit (39.4 nM), and also been applied in real water samples detection. Through mass spectroscopy, single crystal X‐ray diffraction and DFT calculation, we confirmed that two PBI molecules would form a stable complex with one Cu 2+ . After adding GSH, PBI ‐Cu 2+ complex would release the free probe, and the "on‐off‐on" recognition process to achieve continuous detection of Cu 2+ and GSH. Abstract : Herein, we reported using a well‐known ESPT molecule 2‐(2'‐Pyridyl)benzimidazol(PBI ) as a fluorescent probe to detect Cu 2+ and GSH in aqueous solution. PBI presented a rapid fluorescence "ON‐OFF" response on Cu 2+ over other metal cations, with a low detection limit (39.4 nM), and also been applied in real water samples′ detection. Through mass spectroscopy, and single crystal X‐ray diffraction, we confirmed that two PBI molecules would form a stable complex with one Cu 2+ .